When hostility is a norm in International Relations: Emotional deviants and internal enemies in populist media discourse - Kosen, Mustafa Gokcan; Kose, Melike Akkaraca (Sage Publications Ltd, 2026)
This study investigates the normative dimension of emotions within domestic politics for international issues. Focusing on Turkish-Greek relations during a period of heightened tension (June-November 2022), we examine how pro-government media constructs hostility towards Greece as a central emotion norm linked to national identity. Employing corpus-assisted discourse analysis within the framework of the subjective group dynamics model, we analyse how opposition figures are portrayed as deviants who do not embody this emotion norm and marginalized as external to the nation. Our findings highlight the powerful role of emotions in both unifying and dividing domestic politics on foreign policy issues and regarding international actors. Furthermore, the study contributes to understanding of the media's role in populist polarization and political contestation surrounding the emotional dimensions of national identity.
Keywords: Domestic Politics; Emotion Norms; Emotional Polarization; Hostility; International Relations; Media And Populism; Turkey-Greece Relations